Obesity management in primary care: systematic review exploring the influence of therapeutic alliance. (21st April 2021) - Sturgiss, Elizabeth A; O'Brien, Kathleen; Elmitt, Nicholas; Agostino, Jason; Ardouin, Stephen; Douglas, Kirsty; Clark, Alexander M
Abstract: Purpose: To identify the influence of the therapeutic alliance on the effectiveness of obesity interventions delivered in primary care. Method: Systematic review of randomized controlled trials of primary care interventions for adult patients living with obesity. Comprehensive search strategy using the terms 'obesity', 'primary care' and 'intervention' of seven databases from 1 January 1998 to March 2018. Primary outcome was difference in weight loss in interventions where a therapeutic alliance was present. Results: From 10 636 studies, 11 (3955 patients) were eligible. Only one study had interventions that reported all aspects of therapeutic alliance, including bond, goals and tasks. Meta-analysis was not included due to high statistical heterogeneity and low numbers of trials; as per our protocol, we proceeded to narrative synthesis. Some interventions included the regular primary care practitioner in management; very few included collaborative goal setting and most used prescriptive protocols to direct care. Conclusions: We were surprised that so few trials reported the inclusion of elements of the therapeutic alliance when relational aspects of primary care are critical for effectiveness. Interventions could be developed to maximize therapeutic relationships and research reports should describe interventions comprehensively. Systematic review registration number: CRD42018091338 in PROSPERO (International prospective register of systematic reviews).